PERAN KETELADANAN ORANG TUA KRISTEN DALAM PEMBENTUKAN KARAKTER ANAK USIA 6-12 TAHUN DI GEREJA BETHEL TABGHA - Robertus Suryady (JURNAL TABGHA, 2023)
The reality of a child's development and growth necessitates the assistance and guidance of both parents in providing support and serving as exemplary figures. Parents hold the greatest responsibility in the development of the overall existence of their children, including their physical and psychological needs, to enable them to grow and mature towards a harmonious and mature personality. This study is entitled "The Role of Christian Parental Exemplars in the Formation of Character in Children Aged 6-".Over the span of 12 years in the Bethel Indonesia Tabgha Church, an inquiry has been formulated regarding the role of Christian parental leadership and the formation of character in children between the ages of 6 and 12. The purpose of this study is to discover the principles governing the Christian parental exemplar based on biblical values, as well as to investigate the formation of the characters of 6-12 year-old children in the Bethel Indonesia Tabgha Church.This research employed a qualitative approach utilizing literature review and descriptive methods for data collection through interviews, observations, and documentations of six participants.Based on the analysis of the data conducted, the conclusion was drawn that Christian parents play a significant role in shaping the character of children aged 6-12 years old. In shaping the character of a child, Christian parents must comprehend the various types of exemplary roles and character-forming approaches for children aged 6 to 12.